Nanocristais de celulose para preparação de bionanocompósitos com quitosana e carbonos nanoestruturados para aplicações tecnológicas e ambientais - Joao Paulo de Mesquita (2012)
In this work, cellulose nanocrystals (CNCs) were prepared from eucalyptus cellulose pulp and were used as reinforcement material for chitosan biopolymer (CH). In addition, the CNCs were used to form carbon nanostructures through controlled pyrolysis and the carbon nanostructures obtained were use to modify the surface of expanded vermiculite clay (EV). The CNCs were obtained by hydrolysis of eucalyptus cellulose pulp using H2SO4 and characterized with different techniques including TEM, XRD, FT-IR and potentiometric titration. The length and diameter of the CNWs were characterized as being 145 25 nm and 6 1.5 nm, respectively. Potentiometric titration gave 141 mmol.kg-1 of sulfates groups on the whiskers surface. In order to prepare the chitosan/CNCs bionanocomposites, three different strategies were used. Firstly, chitosan/CNCs were prepared using the simple casting method. The effect of different concentrations of CNCs on the mechanical and thermal properties and water absorption capacity of the films were evaluated. It was found that the CNCs were uniformly dispersed throughout the matrix, interacting strongly with the polymer chains of chitosan. These interactions resulted in a strong improvement in the tensile modulus (up to 160%) and in the tensile strength (up to 115%). Also, a significant decrease in water absorption capacity of the biopolymer was measured. The second approach was the preparation of bio-based nanocomposite through covalent linkage between CH and CNCs. These nanocomposites showed similar mechanical properties compared to those observed for materials prepared from the simple casting method. On the other hand, the water resistance properties were considerably enhanced for the CH-graft-CNCs relative to those systems obtained from the casting method. Finally the layer-by-layer (LBL) technique was also used to prepare thin films of chitosan/NCCs. The film growth was followed by UV-vis spectroscopy and showed the deposition of 14.7 mgm-2 of chitosan polymer in each cycle. Scanning electron microscopy showed high density and homogeneous distribution of CNCs adsorbed on each chitosan layer. Cross section characterization of the assembled films indicates an average of ~ 7 nm of thickness per bilayer. The surface of the film also shows a morphology made by laterally aggregated nanowhiskers generating a morphology which looks like a bundle of spaghetti-like fibers. The film surface was also characterized by AFM and showed a relatively smooth surface having the roughness values lower than 11 nm for a film of 140nm. The NCCs were also used in the preparation of carbon nanostructures by pyrolysis at different temperatures. It was found that different pyrolysis temperatures deeply modify the characteristics of the carbon obtained. With the pyrolysis at 300 °C, the CNCs presented an incomplete carbonization, but this sample showed (using HR-TEM) the presence of tubular structures with graphitic order.With increasing pyrolysis temperature to 600 and 900 °C, the tubular structures disappear, and other carbon nanostructures take place, mainly spherical nanoparticles, consisting of amorphous and graphitic carbon. In addition, it was observed a significant increase in specific surface area and volume of micro-and mesopores with increasing temperature of pyrolysis. The materials were then used in the adsorption of bisphenol A. The sample obtained at 900°C (CANCC900) showed a significant affinity for bisphenol A moieties, showing a rapid and high adsorption capacity. The maximum adsorption capacity obtained from the fitting data of the Langmuir isotherm was 1029 mgg-1. This high adsorption capacity was attributed to large surface area and also due to the great accessibility to the surface by the significant amount of mesopores. Finally, the NCCs were dispersed on the expanded vermiculite surface (EV) through the simple control of dipping cycles. The deposition of the NCCs on the surface of the vermiculite was confirmed by FTIR and TG. Subsequently, the composites CNCs/EV were pyrolyzed at 900 °C to form a surface layer of amorphous and nanostructured graphitic carbon. The presence of these carbon nanostructures on the EV surface produced a hydrophobic character on the vermiculite surface and strongly increased the oil absorption capacity for soy bean and engine oil